Automated mechanical cardiopulmonary resuscitation devices versus manual chest compressions in the treatment of cardiac arrest: protocol of a systematic review and meta-analysis comparing machine to human. Issue 2 (15th February 2021) - Obermaier, Manuel; Zimmermann, Johannes B; Popp, Erik; Weigand, Markus A; Weiterer, Sebastian; Dinse-Lambracht, Alexander; Muth, Claus-Martin; Nußbaum, Benedikt L; Gräsner, Jan-Thorsten; Seewald, Stephan; Jensen, Katrin; Seide, Svenja E
Abstract : Introduction: Cardiac arrest is a leading cause of death in industrialised countries. Cardiopulmonary resuscitation (CPR) guidelines follow the principles of closed chest compression as described for the first time in 1960. Mechanical CPR devices are designed to improve chest compression quality, thus considering the improvement of resuscitation outcomes. This protocol outlines a systematic review and meta-analysis methodology to assess trials investigating the therapeutic effect of automated mechanical CPR devices at the rate of return of spontaneous circulation, neurological state and secondary endpoints (including short-term and long-term survival, injuries and surrogate parameters for CPR quality) in comparison with manual chest compressions in adults with cardiac arrest. Methods and analysis: A sensitive search strategy will be employed in established bibliographic databases from inception until the date of search, followed by forward and backward reference searching. We will include randomised and quasi-randomised trials in qualitative analysis thus comparing mechanical to manual CPR. Studies reporting survival outcomes will be included in quantitative analysis. Two reviewers will assess independently publications using a predefined data collection form. Standardised tools will be used for data extraction, risks of bias and quality of evidence. If enough studies are identified for meta-analysis, the measures of association will be calculated by dint of bivariate random-effects models. Statistical heterogeneity will be evaluated by I 2 -statistics and explored through sensitivity analysis. By comprehensive subgroup analysis we intend to identify subpopulations who may benefit from mechanical or manual CPR techniques. The reporting follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Ethics and dissemination: No ethical approval will be needed because data from previous studies will be retrieved and analysed. Most resuscitation studies are conducted under an emergency exception for informed consent. This publication contains data deriving from a dissertation project. We will disseminate the results through publication in a peer-reviewed journal and at scientific conferences. PROSPERO registration number: CRD42017051633.